2005
DOI: 10.1128/jb.187.18.6571-6576.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis ofPseudomonas aeruginosaGrowth: Comparison of Gene Expression in Planktonic Cultures and Developing and Mature Biofilms

Abstract: The transcriptomes of logarithmic-and stationary-phase Pseudomonas aeruginosa planktonic cultures and static biofilms of different stages of development were compared. Developing and confluent biofilm transcriptomes were found to be related to those of logarithmic-and stationary-phase planktonic cultures, respectively. In addition, a number of novel genes were up-regulated in developing and confluent biofilms, including genes encoding putative solute transport proteins and transcriptional regulators, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 29 publications
9
149
3
Order By: Relevance
“…Interestingly, proteomic studies on a P. aeruginosa biofilm revealed the induction of AhpC, together with L-ornithine 5-monooxygenase, whose gene is located within the pvd locus involved in pyoverdine synthesis (Visca et al, 1994;Sauer et al, 2002). In contrast, transcriptome analyses of P. aeruginosa biofilms (Whiteley et al, 2001;Waite et al, 2005) revealed no induction of the pyoverdine genes, except when the gene expression profile of biofilm cells was compared to that of cells released from the biofilm (Sauer et al, 2004). However, only pvcAB appeared to be ironregulated during the planktonic lifestyle, suggesting that iron does not constitute the only signal inducing expression of the biofilm-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, proteomic studies on a P. aeruginosa biofilm revealed the induction of AhpC, together with L-ornithine 5-monooxygenase, whose gene is located within the pvd locus involved in pyoverdine synthesis (Visca et al, 1994;Sauer et al, 2002). In contrast, transcriptome analyses of P. aeruginosa biofilms (Whiteley et al, 2001;Waite et al, 2005) revealed no induction of the pyoverdine genes, except when the gene expression profile of biofilm cells was compared to that of cells released from the biofilm (Sauer et al, 2004). However, only pvcAB appeared to be ironregulated during the planktonic lifestyle, suggesting that iron does not constitute the only signal inducing expression of the biofilm-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although these models do not reflect the complexity found in natural environmental biofilms, monospecies biofilms were the first step towards understanding adaptation to the sessile lifestyle for many bacteria, including two recent studies on L. pneumophila (Mampel et al, 2006;Piao et al, 2006). These models pave the way for the study of complicated microbial interactions and have proven to be useful for assessing the gene expression profile of sessile cells even if the different cell types present within a biofilm cannot be analysed independently by this approach (Schembri et al, 2003;Beloin et al, 2004;Waite et al, 2005;Whiteley et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While our genetic and phenotypic data would suggest that subinhibitory concentrations of colistin influence biofilm formation in P. aeruginosa, no significant difference was observed in biomass using flow cells (data not shown). It is important to note that gene expression varies in P. aeruginosa planktonic cultures relative to the biofilm mode of growth (Waite et al, 2005(Waite et al, , 2006Whiteley et al, 2001). Furthermore, culture conditions may influence the patterns of gene expression in response to subinhibitory concentrations of colistin.…”
Section: Discussionmentioning
confidence: 99%
“…Flow-cell analysis also revealed no difference in biomass or ability to form mushroom structures in the presence of the antimicrobial (data not shown). This may be a reflection of the distinct environments and expression profiles that exist in planktonic cultures and mature biofilms (Waite et al, 2005(Waite et al, , 2006Whiteley et al, 2001). It must also be considered that other genes, which are not responsive to subinhibitory concentrations of colistin under the conditions tested, are required for induction of the biofilm mode of growth.…”
Section: Physiological Consequences Of Colistin-induced Ahqsmentioning
confidence: 99%
“…Several S. aureus genes have been reported to contribute to its biofilm-forming ability, including agr (3)(4)(5), sarA (5-7), sigB (8), ica (9), rbf (10), tcaR (11), arlRS (12,13), and alsSD (14). Microarray analyses of S. aureus (15,16), Pseudomonas aeruginosa (17,18), Bacillus subtilis (19,20), and Escherichia coli (21) have also illustrated that there are major differences in gene expression between biofilm and planktonic cultures of these organisms. These results underscore the need to study biofilm physiology as a way to better understand how the bacteria exist in vivo.…”
Section: O Ne Of the Primary Causative Agents Of Nosocomial Infectionmentioning
confidence: 99%